2012
DOI: 10.1504/ijode.2012.051442
|View full text |Cite
|
Sign up to set email alerts
|

Measuring social capital in creative teams through sociometric sensors

Abstract: Abstract:We describe the results of an experiment capturing the face-to-face "honest signals" of knowledge workers through sociometric badges. We find that collective creativity of teams is a function of the aggregated social capital of members. The higher it is, the higher their creative output. We collected communication data of 14 graduate students and their instructor during a one-week seminar, comparing it against the creative output of their teamwork. As a second component of social capital we also measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…This means that they give more outspoken feedback to each other, which has been shown in earlier research to increase creative performance (Gloor et al, 2012). Therefore, we hypothesize that:…”
Section: H3: the Higher The E-mail Traffic Is The More Successful Ismentioning
confidence: 78%
See 1 more Smart Citation
“…This means that they give more outspoken feedback to each other, which has been shown in earlier research to increase creative performance (Gloor et al, 2012). Therefore, we hypothesize that:…”
Section: H3: the Higher The E-mail Traffic Is The More Successful Ismentioning
confidence: 78%
“…For example, Olguin-Olguin, Gloor and Pentland (2009) used the data collected with these sensors and estimated the daily average length of stay (LOS) as well as number of delays in a Postanesthesia Care Unit (PACU) of a Boston area hospital. Gloor et al (2012) used sociometric badges to investigate the factors enabling collective creativity, looking at individual and collective patterns of social behavior. The authors found that the more team members directly interact with each other face-to-face, and the more they trust other team members, the more creative and of higher quality the result of their teamwork is.…”
Section: Measurement Of Creativitymentioning
confidence: 99%
“…[31] began a study on the creativity within the working groups. They established that the members who had a particular set of character traits were better able to produce quality work and thus create a dynamic group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Początkowo analiza sieci społecznych przeprowadzana była na podstawie ankiet wypełnianych ręcznie przez uczestników (Cummings, 2003), jednak z czasem popularne stały się badania przeprowadzane z zastosowaniem wiadomości e-mail (Aral, 2007). W niektórych badaniach stwierdzono, że zespoły badawcze są bardziej kreatywne, gdy posiadają większy kapitał społeczny (Gloor, 2012).…”
Section: Sieć Społecznaunclassified